PENGARUH KOMPLEKSITAS PERUSAHAAN, RISIKO PERUSAHAAN, DAN OPINI AUDIT TERHADAP AUDIT DELAY - Velia Septia Wulandari; Fitriyah (Publika Citra Media, 2026)
This study aims to determine and analyze the influence of company complexity, company risk, and audit opinion on audit delay in transportation and logistics companies from 2019 to 2024. Company complexity is measured by the number of subsidiaries, company risk is measured using the debt-to-equity ratio (DER), and audit opinion is measured using a dummy variable, where 1 represents an unqualified opinion (WTP) and 0 represents an opinion other than WTP (fair without research). The data used in this study were obtained from the official IDX website and company websites. This study used 15 transportation and logistics companies that had been eliminated according to the specified criteria. The sampling method used in this study was purposive sampling. The data analysis method used panel data regression using Eviews 13.0 software. The results of this study indicate that company complexity, company risk, and audit opinion simultaneously influence audit delay. Partially, the variables of company complexity and company risk influence audit delay. Meanwhile, the variable of audit opinion does not affect audit delay.